2010
DOI: 10.1111/j.1471-4159.2010.06574.x
|View full text |Cite
|
Sign up to set email alerts
|

ATF2 maintains a subset of neural progenitors through CBF1/Notch independent Hes‐1 expression and synergistically activates the expression of Hes‐1 in Notch‐dependent neural progenitors

Abstract: J. Neurochem. (2010) 113, 807–818. Abstract Hes‐1 and Hes‐5 are downstream effectors of Notch signaling that are known to be involved in different aspects of neural stem cell proliferation and differentiation. Evidence has emerged that Hes‐1 expression can be regulated by alternate signaling pathways independent of canonical Notch/CBF1 interaction. This context‐dependent differential regulation of Hes‐1 expression in neural progenitor gains a lot of importance as it would help in its exponential expansion with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…Thus, Hes-1 may be a common substrate of the JNK kinase family in neurons. This speculation is consistent with the report that bFGF2 enhances Hes-1 expression through direct binding of JNK-activating transcription factor 2 (ATF2) to the Hes-1 promoter (Sanalkumar et al, 2010), whereas ATF2 is a downstream target of JNK (Gupta et al, 1995). Moreover, Hes-1 suppression of GluR1 expression decreased calcium influx upon AMPA stimulation in cortical neurons.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, Hes-1 may be a common substrate of the JNK kinase family in neurons. This speculation is consistent with the report that bFGF2 enhances Hes-1 expression through direct binding of JNK-activating transcription factor 2 (ATF2) to the Hes-1 promoter (Sanalkumar et al, 2010), whereas ATF2 is a downstream target of JNK (Gupta et al, 1995). Moreover, Hes-1 suppression of GluR1 expression decreased calcium influx upon AMPA stimulation in cortical neurons.…”
Section: Discussionsupporting
confidence: 80%
“…Whereas early stage Hes1-positive cells were observed to be multipotent, later stage Hes1-positive cells were restricted to the duct and acinar lineages (Kopinke et al, 2011). The implication of this for the role of Notch signaling in endocrine/duct fate patterning versus a specific role of Hes1 in late stage acinar cell progenitors is not yet clear, and might be rooted in Notch-independent control of Hes1 expression (Curry et al, 2006;Ingram et al, 2008;Nakayama et al, 2008;Sanalkumar et al, 2010;Wall et al, 2009), or a later role for Notch/Hes1 within the centroacinar cell type, which is not yet fully formed at the secondary transition. Further evidence for the suppressive effect of Notch signaling on the acinar fate is derived from the inhibitory effect of Notch on the transcriptional activity of the pro-acinar factor Ptf1a (Esni et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have reported that ERK1/2 activation is involved in regulating proliferation of adult hNSCs (58 -60). JNK signaling has been shown to mediate FGF2-stimulated proliferation of embryonic neural stem cells (61). JNK signaling is also involved in differentiation and apoptosis of neural stem cells (62)(63)(64).…”
Section: Discussionmentioning
confidence: 99%